Synergistic effect of boron and chromium on phase transformations and mechanical properties of boron-alloyed cast steel after quenching and tempering - Białobrzeska, Beata; Dziurka, Rafał; Bała, Piotr; Lemecha, Magdalena; Ligier, Krzysztof; Napiórkowski, Jerzy (Journal of materials research and technology, 2025)
The aim of this study was to investigate the synergistic effect of boron and chromium on phase transformations and the mechanical properties of cast steel subjected to quenching and tempering. Two cast steels were developed: one alloyed with both chromium (0.9 wt%) and boron (0.003 wt%), and a reference material containing only boron. Microstructural analysis was performed using light microscopy, scanning electron microscopy, and transmission electron microscopy. Additionally, the kinetics of phase transformations and the mechanical properties were evaluated for various heat treatment conditions, including as-cast, quenched, and quenched and tempered at 200, 400, and 600 °C. Dilatometric studies allowed for the determination of characteristic transformation temperatures and the development of continuous cooling transformation − CCT diagrams. Mechanical properties were assessed via hardness measurements, static tensile tests, and Charpy impact tests. The results indicate that the addition of chromium significantly influences the course of phase transformations by stabilizing austenite and delaying the pearlitic transformation. As a result, the critical cooling rate decreases dramatically—from approximately 262 °C/s to 10 °C/s. Additionally, chromium enhances the strength properties of boron cast steel by increasing its hardness and tensile strength. In the quenched and quenched and tempered at 200 °C states, the chromium alloyed cast steel exhibited hardness and yield strength values exceeding 633 and 550 HBW, and 1220 MPa and 1472 MPa, respectively. However, it should be noted that chromium simultaneously deteriorates the impact toughness of cast steel, which may limit its applicability in environments subjected to high dynamic loads. In the quenched condition, the chromium alloyed cast steel showed a Charpy impact strength of only 6 J/cm2, which increased to 57 J/cm2 after tempering at 600 °C. For comparison, the reference cast steel achieved 34 J/cm2 in the quenched state and 103 J/cm2 after tempering at 600 °C.